Summer mid-day-night composition and abundance of zooplankton from Lake Ikeda, Japan - Shaharudin, Abdul Razak; Toshio, Saisho (Universiti Putra Malaysia Press, 2002)
Variations between midday and midnight in the species composition and abundance of the main zooplankton assemblage of Lake Ikeda, a crater-lake were analyzed during the summer of 1986. The protozoans, comprising more than 70% of the whole zooplankton population were the most abundant followed l7y the rotifers (12%), eopepods (8 %) and cladocerans (7 %). Except for the copepods and a few rotifers, most of the other zooplankton were evident at a slightly higher abundance at night. Total zooplankton abundance was highest during early summer but decreased gradually until the end of summer. Species composition was highest in early summer, and persisted until the middle of summer but gradually decreased with rare occurrences of some species at the end of summer, where some species were either rarely sampled or entirely absent from the samples.